Структура, засоби та вміння усвідомленої саморегуляції музично-виконавської діяльності музикантів-інструменталістів - Черкасов Володимир; Cherkasov Volodymyr; Гербер Анжеліка; Gerber Anzhelika (Видавництво «Код», 2025)
Резюме. У статті здійснено спробу дослідити процес саморегуляції як активність суб’єкта, спрямована на створення та деталізацію образу майбутнього (бажаного, потрібного) стану в системі виконавської діяльності, на адекватне оцінювання реального (теперішнього) стану, а також на знаходження ресурсів, засобів, способів, шляхів з’єднання теперішнього з майбутнім, реального з бажаним.

Abstract. The article attempts to investigate the process of self-regulation as an activity of the subject aimed at creating and detailing the image of the future (desired, necessary) state in the system of performing activity, at adequately assessing the real (present) state, as well as at finding resources, means, methods, ways of connecting the present with the future, the real with the desired.The content of regulatory processes in relation to musical and performing activities is specified, specific circles of skills are highlighted that are necessary for its effective self-regulation, namely: the ability to work on the image of the desired future (the image of oneself as a specialist, the performing image, the image of the desired functional state), to create, transform, enrich, and specify it; the ability to optimally (depending on one’s capabilities and objective circumstances) determine, clearly formulate the goal, specify the conditions for its achievement, determine the necessary and available resources and means of achievement, plan the process of moving towards it; the ability to realize and analyze the current state both in one’s professional and personal development as a specialist musician, and in the situation of real performing activities (the ability to listen to oneself, to realistically evaluate one’s own performance, the ability to perceive and evaluate one’s own psychophysiological state). We consider these skills to be basic, since they ensure the functioning of the regulatory circuit, the fullness of its structural and functional aspect. However, it is also necessary to ensure the fullness of the substantive side of the regulatory process, that is, the brightness, affective coloring, stability, controllability, structural complexity of images, which are the main means of selfregulation of performing activity. This is ensured by a range of skills that we have called additional, namely: the ability to create a polymodal, complex, emotionally colored, meaningful image in the imagination; the ability to purposefully focus on the perceptual-imaginary image, its sides, details; to switch attention to the necessary sides, to distribute it; the ability to use images to regulate emotional states.
Structure, means and skills of conscious self-regulation of musical-performing activity of instrumental musicians
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-16?authuser=0
Keywords: структура; засоби; вміння; саморегуляція; музично-виконавська діяльність; музиканти-інструменталісти